2004
DOI: 10.3386/w10812
|View full text |Cite
|
Sign up to set email alerts
|

Are Investors Naive About Incentives?

Abstract: Traditional economic analysis of markets with asymmetric information assumes that uninformed agents account for the incentives of informed agents to distort information. We analyze whether investors in the stock market internalize such incentives. Stock recommendations of security analysts are likely to be biased upwards, particularly if the issuing analyst is affiliated with the underwriter of the recommended stock. Using the NYSE Trades and Quotations database, we find that large (institutional) traders acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
32
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 16 publications
7
32
0
Order By: Relevance
“…However, the discrepancy between higher upward distortion of recommendations and more downward distortion of forecasts does allow a distinction: In the second step, we link the differences in distortive behavior to different investors' information processing and to different management pressures. Using the New York Stock Exchange Trades and Quotations (TAQ) database (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002), we first confirm the findings of previous literature (Iskoz [2002], Malmendier and Shanthikumar [2007], Mikhail, Walther, and Willis [2007]) that both small and large investors react 5 We also replicate all results using quarterly earnings forecasts and long-term growth forecasts. The data and all results are described in detail in Online Appendix A.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…However, the discrepancy between higher upward distortion of recommendations and more downward distortion of forecasts does allow a distinction: In the second step, we link the differences in distortive behavior to different investors' information processing and to different management pressures. Using the New York Stock Exchange Trades and Quotations (TAQ) database (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002), we first confirm the findings of previous literature (Iskoz [2002], Malmendier and Shanthikumar [2007], Mikhail, Walther, and Willis [2007]) that both small and large investors react 5 We also replicate all results using quarterly earnings forecasts and long-term growth forecasts. The data and all results are described in detail in Online Appendix A.…”
supporting
confidence: 78%
“…Following Lee and Radhakrishna [2000], we choose dollar-rather than share-based cutoffs since they minimize noise in separating individuals from institutions, and allow for a buffer zone ($20,000-$50,000) between small and large trades. 21 Malmendier and Shanthikumar [2007] show that these proxies are effective measures of individual and institutional trades until about 2000. As they discuss, the small portfolio size of most individual investors ensured that their trades remained below $50,000, and the distribution of trade sizes on the NYSE remained quite stable from 1993 through 2000.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…2 As argued by Malmendier and Shanthikumar [18], these differences seem to indicate heterogeneity in the level of strategic sophistication among investors. In controlled laboratory experiments, Dickhaut et al [10] and Cai and Wang [5] document heterogeneous strategic sophistication in the responses to the same message.…”
Section: Introductionmentioning
confidence: 99%
“…Smart investors recognize such distortion and can discount the recommendations to de-bias the transmitted information. However, other investors may be too naïve to recognize such distortions (e.g., Malmendier and Shantikumar (2007) Harrison and Kreps (1978) suggested that in a dynamic environment with time-varying heterogeneous beliefs and short-sales constraints, an asset buyer may be willing to pay more than his own expectation of the asset's fundamental. This is because he holds the option of reselling the asset to other more optimistic buyers for a speculative profit in the future.…”
Section: Distorted Information Transmissionmentioning
confidence: 99%